The South China Sea Conflict and Security Cooperation in ASEAN Waters - Rifqi Setia Wardhana (Department of International Relations, University of Mataram, 2021)
The study aims to analyze how ASEAN acts to keep the region from conflicts over the South China Sea. The South China Sea conflict is a conflict that has a major impact on the ASEAN region; it is influenced by the territorial waters owned by several countries in ASEAN according to the United Nations Convention for the Law of the Sea (UNCLOS) in 1982. China’s unilateral claim in 2012 was the beginning of ASEAN’s concerns over the security and stability around the South China Sea and ASEAN waters. This article focuses on ASEAN’s response in response to China’s moves after unilateral claims and the establishment of military fleets around the Spratly and Paracel islands. The ASEAN Regional Forum (ARF) on 2018 is an important response for ASEAN in the face of maritime security threats. Establishment of policy strengthening security cooperation will have a significant impact in the development of stability in the South China Sea region, where the situation in the region worsen with the increasing number of actors involved in the conflict. The findings obtained from this paper aim to explain the analysis of ASEAN schemes to safeguard the territorial waters around the South China Sea.